From discussion to action: Characterizing areas of reform in Latin America and the Caribbean - Sebastian Bustos; Luis Felipe Céspedes; John León-Díaz; María Orduz (Inter-American Development Bank (IDB), 2023)
Structural reforms modify the institutional and regulatory framework to foster economic growth and improve welfare. While initially linked to economic liberalization, the concept has expanded to encompass a more comprehensive array of sector-specific interventions. However, the increased level of detail in these reforms presents significant challenges in accurately identifying the specific type of reform implemented by each country. In this study, we employ a comprehensive analysis of the policy discussions in Article IV Staff Reports of the International Monetary Fund to shed light on the dynamic nature of reforms and unveil regional disparities in reform priorities. The findings demonstrate a notable shift in Latin American and the Caribbean countries, where there is a growing emphasis on reforms that prioritize transparency, enhance institutional quality, advance education and healthcare systems, and strengthen safety nets.
Keywords: C82; O2; O4; 330; Structural reforms; narrative approach; text analysis